STRENGTHENING TECHNOLOGICAL LITERACY IN JUNIOR HIGH SCHOOL TEACHERS IN THE INDUSTRIAL REVOLUTION ERA 4.0 - Soewarto Hardhienata; Yudhie Suchyadi; Dian Wulandari (UNIVERSITAS PAKUAN, 2021)
This study aims to find a model of strengthening technological literacy in junior high schools. This study used descriptive qualitative method. Data were collected through observation and interviews with teachers in junior high schools in the Bogor city area. This study found a model of strengthening technological literacy. This model includes elements of communication and collaboration in the form of active participation in learning and research activities. It consists of components of individual competence in the form of usage skills, critical understanding, and communicative abilities. This research contributes to the model of strengthening technological literacy for junior high school teachers in the Bogor City area.